Policy Model for Fair Corporate Social Responsibility Management in Indonesia - Nathan M. Siahaan, Lego Karjoko, Hari Purwadi (International Journal of Advanced Science and Technology, 2020)
This research examined the model of legal policy of CSR in Indonesia to be effectively and beneficially implemented for companies, community and environments. This is a normative research using statute approach, historical approach and comparative approach. The data obtained from the research were grouped in accordance with each variable to be analyzed qualitatively and presented in analytical descriptive form. The result of this research showed that the model of CSRlegal policy in Indonesia is mandatory and supported by proper sanctions. The change of paradigm regarding Human Right that makes company as the one responsible for the ecosob is a strong supporting factor for the legal policy of CSR in Indonesia. Keyword: Model of legal policy; corporate social responsibility.